Evaluasi Kebijakan Dana BOS Di Lingkungan Suku Dinas Pendidikan Wilayah II Kota Administrasi Jakarta Barat - Arif, Zaenal; Wicaksana, Harits Hijrah; Mariam, Siti; Nefianto, Tirton (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Evaluation of the BOS Fund policy is a central government policy, in this case the Ministry of Education and Culture, where the BOS Fund is allocated to help economically disadvantaged communities, in this case students from schools. The aim of this research is to find out the evaluation of the implementation of School Assistance Funds (BOS) within the Region II Education Sub-Department of West Jakarta Administrative City. The method used in this research is a descriptive qualitative method. The results of this research are: First, in terms of transparency and accountability, the West Jakarta Sub-dept. succeeded in building a clear and easily accessible system for managing BOS funds. In terms of stakeholder participation and involvement, the West Jakarta Sub-department succeeded in involving related parties, such as school committees, teachers, parents and the local community. In reporting the use of funds, the West Jakarta Sub-department shows superior performance by compiling regular reports in accordance with applicable regulations.